PENGENALAN PUPUK ORGANIK PADA KELOMPOK PEMUDA DI DESA TELAGA PACA KECAMATAN TOBELO SELATAN KABUPATEN HALMAHERA UTARA - Hunila, Ernny; Dilago, Zakarias; Kastanja, Ariance Yeane (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
The community service activities that have been carried out aim to increase community knowledge about organic farming and organic fertilizer as well as skills in how to make organic fertilizer to support community agricultural management. The methods used in this service activity are counseling, discussion and demonstration of making solid organic fertilizer. The solid organic fertilizer made is organic fertilizer based on livestock manure and gamal leaves. The tools used in making fertilizer are shovels, hoes, buckets, scales, tarpaulins and drums, while the materials used are livestock manure, granulated sugar, EM4, water. The results of the activity show an increase in knowledge and skills in making organic fertilizer